Adenovirus vector expressing keratinocyte growth factor using CAG promoter impairs pulmonary function of mice with elastase‐induced emphysema. (13th July 2017) - Oki, Hiroshi; Yazawa, Takuya; Baba, Yasuko; Kanegae, Yumi; Sato, Hanako; Sakamoto, Seiko; Goto, Takahisa; Saito, Izumu; Kurahashi, Kiyoyasu
ABSTRACT: Pulmonary emphysema impairs quality of life and increases mortality. It has previously been shown that administration of adenovirus vector expressing murine keratinocyte growth factor (KGF) before elastase instillation prevents pulmonary emphysema in mice. We therefore hypothesized that therapeutic administration of KGF would restore damage to lungs caused by elastase instillation and thus improve pulmonary function in an animal model. KGF expressing adenovirus vector, which prevented bleomycin‐induced pulmonary fibrosis in a previous study, was constructed. Adenovirus vector (1.0 × 10 9 plaque‐forming units) was administered intratracheally one week after administration of elastase into mouse lungs. One week after administration of KGF–vector, exercise tolerance testing and blood gas analysis were performed, after which the lungs were removed under deep anesthesia. KGF‐positive pneumocytes were more numerous, surfactant protein secretion in the airspace greater and mean linear intercept of lungs shorter in animals that had received KGF than in control animals. Unexpectedly, however, arterial blood oxygenation was worse in the KGF group and maximum running speed, an indicator of exercise capacity, had not improved after KGF in mice with elastase‐induced emphysema, indicating that KGF‐expressing adenovirus vector impaired pulmonary function in these mice. Notably, vector lacking KGF‐expression unit did not induce such impairment, implying that the KGF expression unit itself may cause the damage to alveolar cells. Possible involvement of the CAG promoter used for KGF expression in impairing pulmonary function is discussed.